Can AI Make Decisions About Rare Diseases? A Critical Examination - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2021)
The Promise and Peril of Artificial Intelligence in Orphan Conditions The journey to a diagnosis for a rare disease—a condition affecting fewer than 1 i...
Keywords: Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine; Machine Learning